Analysis of science, technology, and innovation in emerging economies (2019)
This book outlines a number of different perspectives on the relationship between science, technology, and innovation in emerging economies. In it, the authors explore the aforementioned relationship as a pillar of economic development, driving growth in emerging economies. Employing a collaborative and interdisciplinary approach, the authors work to determine the main related factors and outcomes of the relationship between science, technology, and innovation, ultimately seeking to guide public policies to enhance the welfare of the population of an emerging economy.